The Combined Clinical Efficacy and Safety Analysis of Adoptive Immunotherapy with Radiotherapy and Chemotherapy in Non-Small-Cell Lung Cancer: Systematic Review and Meta-Analysis - Zhiming Fan; Honggui He; Liqun Chen (Applied Bionics and Biomechanics)
Objective. To explore the differential efficacy of chemoradiotherapy combined with adoptive immunotherapy and radiochemotherapy alone in patients with non-small-cell lung cancer (NSCLC). Methods. Qualified randomized controlled trial (randomized controlled trial, RCT), or nonrandomized concurrent controlled trial (NRCCT), published in various databases, including PubMed, EMBASE, Chinese journal full-text database, Medline, Cochrane database, and VIP Chinese database, and the Revman5. 0 software performed the data analysis. Results. We found the significantly different curative effect between the experimental and control groups (OR=1.94, 95% CI (1.46, 2.58), P<0.001, I2=0%, Z=4.59), effect of adoptive immunotherapy on the progression of disease (OR=1.80, 95% CI (1.38, 2.35), P<0.001, I2=0%, Z=4.33), adoptive immunotherapy on overall survival (OR=2.19, 95% CI (1.60, 2.99), P<0.001, I2=0%, Z=4.91), and adverse effects of adoptive immunotherapy (OR=1.76, 95% CI (1.25, 2.48), P=0.001, I2=0%, Z=3.26). Conclusion. Adoptive immunotherapy combined with microradiotherapy can decrease the recurrence of NSCLC and improve patient survival, as well as early patients can be benefited more significantly from immunotherapy.